Variabilidade da frequência cardíaca e seu valor prognóstico imediato em nefropatas crônicos submetidos à hemodiálise - Gatti, Márcio (2015)
Chronic Renal Failure (CRF) is a metabolic syndrome resulting in progressive loss of ability to renal excretion. In advanced stages dialysis is necessary. The introduction of new technological advances in hemodialysis made this procedure safe and able to maintain patients' lives for long periods. However, in 30% of the hemodialysis, may occur some kind of complication. The heart rate variability (HRV) reveals information on the functional state of the autonomic nervous system and reflects the balance between the sympathetic and parasympathetic branches of the same. HRV analysis have been proposed as a component of the clinical evaluation for risk stratification of patients. HRV can be studied by linear methods, time domain and frequency and nonlinear methods in the field of chaos. Objective: Assess whether or not there is an association between lower HRV immediately preceding the hemodialysis and the occurrence of complications during or after the same period. Casuistic and Method: 44 unselected patients were included in the study, regardless of sex and age being 15 (34.1%) were female and 29 patients (65.9%) males, with 61.7 ± 14.5 years. Inclusion criteria were considered just the fact of having IRC, be in regular program of performing hemodialysis in the dialysis unit at Hospital de Base (HB) of São José do Rio Preto. The methodology consisted of the assessment of HRV in the time, frequency and chaos, using registration electrocardiographic time series with the aid of equipment Polar RS800CX for 20 minutes moments before initiating hemodialysis session. The 44 patients were followed throughout the dialysis period by verifying the occurrence of complications. Results: 35 patients (NC) had no complications during hemodialysis, while 9 patients (C) had complications, such as hypotension, hypoglycemia, and cramps. The results showed no association between lower HRV with the occurrence of complications during or after hemodialysis. But it was evident that the diabetic patients had a higher probability of complications, because it was the only variable that showed a statistically significant difference. Comparing the results of HRV in diabetic patients with nondiabetic patients, we found lower values for the variables that represent the sympathetic autonomic activity, such as SDNN, LF, SD2 and alpha 1. Conclusions: HRV in the time, frequency and chaos was not characterized as a predictor of the occurrence of complications during or after hemodialysis. However, in diabetic patients there is a significant reduction in the sympathetic component associated with the occurrence of complications, highlighting the possibility of using a simple, noninvasive method for determining prognosis by studying HRV.